2006
DOI: 10.1074/jbc.m602237200
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Induction of Prostate Cancer Cell Invasion Is Mediated by Ezrin

Abstract: Ezrin is a key signaling molecule that regulates cell survival, adhesion migration, and invasion. We have previously shown that ezrin is regulated by androgen in rat prostate and that its expression is increased in prostate cancer and in prostate intraepithelial neoplasia. We have used the androgen-sensitive cell line LNCaP-FGC to investigate the role of ezrin in androgeninduced cell invasion. We found that androgen treatment of LNCaP-FGC cells induces ezrin expression, an effect that is inhibited by the andro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 56 publications
4
83
1
Order By: Relevance
“…Ezrin Ezrin and hepatocellular carcinoma D Okamura et al is highly expressed in several types of human cancers and correlations between its immunoreactivity and patient outcome have been shown. 28 Several in vitro 29,30 studies have demonstrated that ezrin is involved in cancer cell invasion, migration, adhesion and proliferation, which may contribute to aggressive tumor progression and early recurrence after surgery. In hepatocellular carcinoma, Zhang et al 14 have reported that ezrin expression was obviously upregulated in several cell lines with high metastatic potential, including MHCC97-H, in which CK19 expression was also identified, 31 and was associated with cell proliferation, migration, and invasiveness.…”
Section: Ezrin and Hepatocellular Carcinoma D Okamura Et Almentioning
confidence: 99%
“…Ezrin Ezrin and hepatocellular carcinoma D Okamura et al is highly expressed in several types of human cancers and correlations between its immunoreactivity and patient outcome have been shown. 28 Several in vitro 29,30 studies have demonstrated that ezrin is involved in cancer cell invasion, migration, adhesion and proliferation, which may contribute to aggressive tumor progression and early recurrence after surgery. In hepatocellular carcinoma, Zhang et al 14 have reported that ezrin expression was obviously upregulated in several cell lines with high metastatic potential, including MHCC97-H, in which CK19 expression was also identified, 31 and was associated with cell proliferation, migration, and invasiveness.…”
Section: Ezrin and Hepatocellular Carcinoma D Okamura Et Almentioning
confidence: 99%
“…As shown in Figures 1a and b, treatment of LNCaP-FGC PCa cells with synthetic androgen R1881 increased c-Myc mRNA and protein levels within 2 h of treatment and this effect was sustained for at least 8 h. The effect of R1881 was blocked by the AR antagonist bicalutamide, indicating the involvement of the AR. Because ezrin is required for androgen-induced invasion (Chuan et al, 2006), we measured ezrin levels in c-Myc expressing cells. As we have previously demonstrated, androgens treatment increases ezrin levels (Chuan et al, 2006).…”
Section: C-myc Regulates Pca Cells Invasion In Vitromentioning
confidence: 99%
“…Because ezrin is required for androgen-induced invasion (Chuan et al, 2006), we measured ezrin levels in c-Myc expressing cells. As we have previously demonstrated, androgens treatment increases ezrin levels (Chuan et al, 2006). This effect could be mimicked by c-Myc overexpression alone, in the absence of hormone, and was enhanced on androgen treatment ( Figure 1c).…”
Section: C-myc Regulates Pca Cells Invasion In Vitromentioning
confidence: 99%
See 2 more Smart Citations